Transverse Momentum, Centrality, and Participant Nucleon Number Dependence of Elliptic Flow - Bao-Chun Li; Yuan-Yuan Fu; Li-Li Wang; Fu-Hu Liu (Advances in High Energy Physics)
In the combined framework of a multisource and participant-spectator model, we study the elliptic flow as a function of transverse momentum and number of participating nucleons in